The structure and musculature of male terminalia in the Palaearctic and Indo-Australian species of the eupitheciine genera Eupithecia Curtis, Gymnoscelis Mabille, and Pasiphila Meyrick (Lepidoptera: Geometridae: Larentiinae) - Schmidt, Olga (Zootaxa, 2020)
Eupitheciini is a diverse cosmopolitan tribe of larentiine moths. The structure and musculature of the male terminalia were described in six Palaearctic and Indo-Australian eupitheciine species from the genera Eupithecia Curtis, Gymnoscelis Mabille, and Pasiphila Meyrick (Lepidoptera: Geometridae: Larentiinae). The tergal flexors of the valvae, muscles m4, running to the medial part of the transtilla or to the membrane dorsad of the transtilla are identified as a potential synapomorphy for the tribe Eupitheciini. The tergal extensors of the valvae, muscles m3(2), running deep into the costa valvae is a possible synapomorphy for the genus Gymnoscelis. The genus Pasiphila does not share all eupitheciine characters, with the tergal flexors of the valvae, muscles m4, extending from the dorsal parts of the vinculum. The Eupithecia haworthiata species-group differs from other species-groups by the shape of the uncus and the sternal extensors of the valvae, muscles m8(3), with lateral fibres longer than the medial ones.